Risk, Robustness and Water Resources Planning Under Uncertainty. Issue 3 (12th March 2018) - Borgomeo, Edoardo; Mortazavi‐Naeini, Mohammad; Hall, Jim W.; Guillod, Benoit P.
Abstract : Risk‐based water resources planning is based on the premise that water managers should invest up to the point where the marginal benefit of risk reduction equals the marginal cost of achieving that benefit. However, this cost‐benefit approach may not guarantee robustness under uncertain future conditions, for instance under climatic changes. In this paper, we expand risk‐based decision analysis to explore possible ways of enhancing robustness in engineered water resources systems under different risk attitudes. Risk is measured as the expected annual cost of water use restrictions, while robustness is interpreted in the decision‐theoretic sense as the ability of a water resource system to maintain performance—expressed as a tolerable risk of water use restrictions—under a wide range of possible future conditions. Linking risk attitudes with robustness allows stakeholders to explicitly trade‐off incremental increases in robustness with investment costs for a given level of risk. We illustrate the framework through a case study of London's water supply system using state‐of‐the ‐art regional climate simulations to inform the estimation of risk and robustness. Plain Language Summary: Faced with pressures from rising populations, competing demands, limited budgets, and climate change, water managers find it increasingly difficult to identify investments to cost‐effectively secure water supplies. Traditional approaches to identify water‐related investments suggest that water managers should invest up to the point where the benefit of an investment, for instance to reduce the risk of water shortages, equals the cost of achieving that benefit. However, some of the uncertainties around future climate change and population growth mean that this approach, called cost‐benefit analysis, will not tell water managers all they need to know with regards to their investment's ability to provide secure water supplies. This study combines traditional investment planning based on cost‐benefit analysis with recent advances in decision‐making under uncertainty to show how water managers can identify investments that are resilient to future uncertainties, including climate change and population growth. London, a city of global significance, is taken as a case study. A computer model of London's water supply system is developed and then computer simulations are run to unravel investments that secure supplies under a wide range of uncertainties. Key Points: Cost‐benefit analysis of water resources investments is expanded to include concepts of robustness to uncertainty Developed framework where stakeholders can trade‐off cost, risk reduction, and robustness requirements of water investments Different decisions are reached and different levels of robustness are attained under different risk attitudes